(untitled) (Vietnam Journal of Community Medicine, 2023)
Background: Atrioventricular nodal re-entrant tachycardia, atrioventricular re-entrant tachycardia and atrial tachycardia are the most popular types of supraventricular tachycardia (SVTs). These are common arrhythmias in practice with various clinical features especially in the elderly. Therefore, an electrophysiology study is critical to identify the diagnosis and treatment if medications do not work. However, the study is deficient of in this problem. Objectives: To describe the clinical features and electrophysiology of SVTs in the elderly compared to the youngers. Subjects and methods: A consecutive study including 107 patients over 60 years old and 302 younger ones. They were studied in the EP lab in university medical center from 1/2017 to 12/2020. Results: 67.2% were AVNRT and the others were AVRT (manifest and concealed pathways). The most prevalent symptoms were fatigue (86%), palpitation (82.2%), and chest discomfort (27.1%), syncope and hypotension 4.7% and 7.5% respectively. In the AVNRT group, elderly patients showed a longer basic cycle length, AH interval, effective refractory period of orthodromic atrioventricular nodal, and slow and fast pathways compared to the young group. On the contrary, in the AVRT group, both tachycardia cycle length and AH interval of the elderly were longer than the under 60 y.o group. Conclusion: SVTs express diverse clinical features in the elderly. Many electrophysiology characteristics were significantly different from the younger ones.